2017
DOI: 10.1111/1471-0528.14673
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopic excision of symptomatic myometrial adenomyosis: feasibility and effectiveness

Abstract: Hysteroscopic excision is feasible for patients with symptomatic adenomyosisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Future studies should include a large population of women with a preoperative transvaginal ultrasound measure of endometrial penetration before undergoing TCRE. Ultrasound-guided resection [31] and routine IUD insertion after resection may further improve the outcome after endometrial ablation [32,33].…”
Section: Commentmentioning
confidence: 99%
“…Future studies should include a large population of women with a preoperative transvaginal ultrasound measure of endometrial penetration before undergoing TCRE. Ultrasound-guided resection [31] and routine IUD insertion after resection may further improve the outcome after endometrial ablation [32,33].…”
Section: Commentmentioning
confidence: 99%
“…Therefore, she underwent hysteroscopic excision of myometrial adenomyotic lesions combined with intraoperative replacement of LNG-IUS, as reported previously. 30 The most obvious advantage of hysteroscopic resection of adenomyotic lesions is that it is especially appropriate for adenomyosis in which adenomyotic lesions are located in the inner muscular layer. Until now, the patient was very satisfied with the MVJ score of two.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other surgery procedures [ 11 , 14 16 ], the greatest advantage of this operation of U-shaped myometrial excavation and modified suture approach with uterus preservation was full consideration of the uterine anatomy. We noticed that once the uterus was excised along the median sagittal plane, the adenomyosis lesion was entirely exposed to us.…”
Section: Discussionmentioning
confidence: 99%